Pengaruh Melodic Intonation Therapy terhadap Kemampuan Fungsional Komunikasi pada Pasien Stroke dengan Afasia Motorik - Naylil Mawadda Rohma (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2020)
Latar Belakang: Afasia adalah kehilangan atau penurunan keterampilan komunikasi dan bahasa yang merupakan akibat dari kerusakan otak (biasanya di belahan otak kiri) dan terjadi pada lebih dari sepertiga orang yang selamat dari stroke.Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh Melodic Intonation Therapy terhadap kemampuan fungsional komunikasi pada pasien stroke dengan afasia motorik.Metode: metode yang digunakan adalah quasy eksperimen pre and post test dengan desain kelompok kontrol dengan teknik purposive sampling dengan jenis consecutive sampling yang kemudian kelompok intervensi dan kelompok kontrol ditentukan menggunakan simple random sampling. Instrumen yang digunakan untuk menilai kemampuan fungsional komunikasi adalah DFCS (Derby Functional Communication Scale). Responden berjumlah 23 orang (12 kelompok intervensi dan 11 kelompok kontrol. Penentuan afasia motorik menggunakan instrumen TADIR (Tes Aphasia untuk Diagnosis Informasi Rehabilitasi).Hasil: Hasil uji-t independen diperoleh nilai p 0,08 yang berarti tidak ada efek Melodic Intonation Therapy pada kemampuan fungsional komunikasi pada pasien stroke dengan motor afasia. Kata kunci : stroke, afasia motorik, kemampuan fungsional komunikasi, melodic intonation therapy   ABSTRACTIntroduction: Aphasia is a loss or decrease in communication skills and language that is a result of brain damage (usually in the left hemisphere) and occurs in more than a third of people who survive strokeObjective: This study aimed to determine the effect of melodic intonation therapy on the functional ability of communication in stroke patients with aphasia motor.Method: the method used is a quasy experiment pre and post test with control group design with a purposive sampling technique with the type of consecutive sampling which then the intervention group and the control group were determined using simple random sampling. The instrument used to assess the functional ability of communication is DFCS (Derby Functional Communication Scale). Respondents numbered 23 people (12 intervention groups and 11 control groups. Aphasia motor determination using the TADIR (Aphasia Test for Rehabilitation Information Diagnosis) instrument.Results: The independent t-test results obtained p value 0.08 which means there is no effect of melodic intonation therapy on the functional ability of communication in stroke patients with aphasia motor.Conclusion: The role of nurses as collaborators is very important because the knowledge of nurses will help bridge patients with speech therapists in interprofessional collaboration. Nurses can help in the availability of data on stroke patients with motor aphasia and therapy and provide education to the family in fulfilling the functional capabilities of communication communication as a basic human need. Keywords: stroke, motor aphasia, communication functional ability, melodic intonation therapy